ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DALAM PEMBUATAN SURAT KETERANGAN AHLI WARIS DI KELURAHAN BENTENG - Melani; Sapri; Adnan, Andi Astinah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to analyze the quality of public services in relation to community satisfaction in the issuance of inheritance certificates at Benteng Urban Village. The main focus of this research is to identify service quality based on the five SERVQUAL dimensions developed by Parasuraman, Zeithaml, and Berry (reliability, responsiveness, tangibles, empathy, and assurance), as well as to identify the factors influencing community satisfaction, namely planning, leadership, coordination, and supervision. This research employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation involving seven informants who have previously processed inheritance certificates at Benteng Urban Village. The results show that the dimensions of reliability and responsiveness were the most frequently criticized by the public due to unclear procedures and a lack of promptness from service staff in providing information. Meanwhile, the aspects of tangibles, assurance, and empathy showed relatively good results. In terms of public satisfaction, it was found that insufficient planning and weak leadership among staff contributed to slow and inefficient service delivery. The conclusion of this study highlights the importance of improving overall service quality, particularly in the areas of communication, staff training, and responsive leadership, in order to enhance public satisfaction